2021
DOI: 10.3390/ma14237265
|View full text |Cite
|
Sign up to set email alerts
|

Eu-Doped Zeolitic Imidazolate Framework-8 Modified Mixed-Crystal TiO2 for Efficient Removal of Basic Fuchsin from Effluent

Abstract: Zeolitic imidazolate framework-8 (ZIF-8) was doped with a rare-earth metal, Eu, using a solvent synthesis method evenly on the surface of a mixed-crystal TiO2(Mc-TiO2) structure in order to produce a core–shell structure composite ZIF-8(Eu)@Mc-TiO2 adsorption photocatalyst with good adsorption and photocatalytic properties. The characterisation of ZIF-8(Eu)@Mc-TiO2 was performed via X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray photoelectron spectros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
2
3
0
Order By: Relevance
“…XRD measurements of the obtained sample confirmed the formation of ZIF-8 crystals on the polyimide substrate, and a characteristic peak originating from (110) plane of ZIF-8 was observed around 7.3 degrees, and all other peaks with weak intensity were assigned to the simulated ZIF-8 and halo patterns of the polyimide (Figure 1C). Moreover, XPS measurement of the obtained sample showed that the binding energy of 2p 3/2 orbital of Zn was observed at 1022.0 eV, which is consistent with the literature value [43], indicating the formation of ZIF-8 crystals (Figure S1A). of Zn was observed at 1022.0 eV, which is consistent with the literature value [43], indicating the formation of ZIF-8 crystals (Figure S1A).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…XRD measurements of the obtained sample confirmed the formation of ZIF-8 crystals on the polyimide substrate, and a characteristic peak originating from (110) plane of ZIF-8 was observed around 7.3 degrees, and all other peaks with weak intensity were assigned to the simulated ZIF-8 and halo patterns of the polyimide (Figure 1C). Moreover, XPS measurement of the obtained sample showed that the binding energy of 2p 3/2 orbital of Zn was observed at 1022.0 eV, which is consistent with the literature value [43], indicating the formation of ZIF-8 crystals (Figure S1A). of Zn was observed at 1022.0 eV, which is consistent with the literature value [43], indicating the formation of ZIF-8 crystals (Figure S1A).…”
Section: Resultssupporting
confidence: 89%
“…Moreover, XPS measurement of the obtained sample showed that the binding energy of 2p 3/2 orbital of Zn was observed at 1022.0 eV, which is consistent with the literature value [43], indicating the formation of ZIF-8 crystals (Figure S1A). of Zn was observed at 1022.0 eV, which is consistent with the literature value [43], indicating the formation of ZIF-8 crystals (Figure S1A). Our previous approach using a NaNO3 additive led to the rapid elution of doped Zn 2+ at the initial stage of the reaction, resulting in the formation of a large amount of free Zn 2+ in the reaction solution.…”
Section: Resultssupporting
confidence: 89%
“…Titanium dioxide (TiO 2 ) was reported in 1972 as a prospective material for photocatalytic water splitting [1]. TiO 2 is one of the most studied and applied photocatalytic materials with low cost, nontoxicity, stability, and diversity of applications [2][3][4][5][6][7][8][9][10][11][12][13][14]. The fundamental mechanism of photocatalysis water splitting is dependent on the formation of photogenerated charge.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, heterogeneous photocatalysis has emerged as a promising pathway for advancing green technologies, particularly in the domains of photocatalytic water splitting, the degradation of hazardous organic pollutants, and the manifestation of robust antibacterial properties [1,2]. The comprehensive investigation underscores the significance of TiO 2 -based materials, attributing their appeal to environmentally benign attributes such as non-toxicity, stability, cost-effectiveness, and wide-ranging applicability [3][4][5][6][7][8][9][10][11][12][13][14][15]. Central to photocatalysis are mechanisms involving the generation of photogenerated charges, encompassing processes such as photo-induced charge separation, bulk and surface charge recombination, and surface charge reactions [16].…”
Section: Introductionmentioning
confidence: 99%